Towards novel BIOmarkers to diagnose SEPsis (BIOSEP) in the emergency room: a protocol for a multicentre, prospective cohort study - Tom van der Poll; W Joost Wiersinga; Michiel Schinkel; Renee A Douma; Hazra S Moeniralam; Marleen A Slim; Evelien Reijnders; Oren Turgman; Sebastiaan C M Joosten; Hessel Peters-Sengers (BMJ Open)
Introduction The international Surviving Sepsis Campaign guidelines highlight the need for recognising sepsis in a timely and accurate manner. Early diagnosis and treatment of sepsis are crucial and associated with reduced mortality. In the early stages of sepsis, heterogeneous clinical signs are difficult to interpret, often leading to missed or delayed diagnoses, as well as inappropriate or late use of antibiotics. There is an urgent need to quickly and accurately identify patients with potential infection in the emergency department (ED) who are at risk of progressing along the infection-sepsis spectrum. This study aims to compare the immune responses of ED patients presenting with a (suspected) infection, both with and without sepsis, to gain insights into immune aberrations and identify novel biomarkers linked to an increased risk of developing sepsis and its sequelae.Methods and analysis A prospective observational cohort study across three hospitals in the Netherlands will be conducted. Adults presenting to the ED of these hospitals, with a (suspected) infection and a Modified Early Warning Score of 2 or higher, will be eligible for enrolment. We aim to include up to 3330 patients. The main study parameters will be characterisation of the host immune and metabolic response using multiomics analysis, Raman spectroscopy, mass spectrometry and gut microbiota profiling in relation to clinical outcomes such as 30-day mortality, length of hospital stay, readmission and postsepsis sequelae.Ethics and dissemination Verbal and written informed consent will be obtained from all participants or their legal representatives. The study was approved by the Amsterdam University Medical Centre Ethics Committee (No. 2022.0279) and will adhere to the Declaration of Helsinki and the Medical Research Involving Human Subjects Act (WMO). Research results will be published in peer-reviewed journals.Trail registration number ClinicalTrials.gov, NCT06178822.